Falling Behind: Has Rising Inequality Fueled the American Debt Boom? - Moritz Drechsel-Grau; Fabian Greimel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We want to explain the rise of household debt in the US since 1980. We present a mechanism that is consistent with the following stylized facts: (i) Real mortgage debt, (ii) debt-service-to-income ratios and (iii) house sizes (in sqft) have increased since the 1980 across all income quintiles. This is despite (iv) real incomes have stagnated for the bottom 50% since the 1980s. Our mechanism is based on other-regarding preferences. Rich agents upgrade their houses to match their risen incomes. Poorer agents want to substitute future consumption for a bigger house today (in order to “keep up with the richer Joneses”). Holding prices constant, debt will necessarily increase since houses are durable and require large payment upfront, but only low maintenance costs in the future. We build a tractable model consistent with these facts and extend it to quantitative a model to show that the partial equilibrium results go through in general equilibrium.
Keywords: D14; D31; E21; E44; E70; 330; household debt; debt boom; social comparisons; consumption network; keeping up with the Joneses